PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS SMART APPS CREATOR (SAC) PADA MATERI EKOSISTEM KELAS 5 SEKOLAH DASAR - Aulia, Putri; Wahyudi; Nara Setya Wiratama (IJPSE Indonesian Journal of Primary Science Education, 2025)
This study aims to develop interactive multimedia learning media based on Smart AppsCreator (SAC) for ecosystem material in Natural Sciences (IPA) subjects for fifth gradestudents at SDN Satak 2. The development method used is the ADDIE model whichincludes five stages: Analysis, Design, Development, Implementation, and Evaluation.Data collection techniques include observation, questionnaires, and tests. The researchsubjects consisted of 8 students in the limited trial and 20 students in the extensive trial.The results of the study showed that: (1) the media was declared very valid with avalidation value of 88% from media experts and 89% from material experts; (2) the mediawas considered very practical with teacher response results reaching 94% and studentresponses of 84.5%; (3) the media was effective, indicated by classical learning completionof 87% in the limited trial and 83% in the extensive trial, exceeding the KKTP (Criteriafor Achieving Learning Objectives) of 75. Based on the research results it can be concludedthat Smart Apps Crelratolr (SAC) -based multimedia is feasible and supports learning onecosystem topics for elementary school students